ANALISIS PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP TINGKAT PENGHINDARAN PAJAK (Studi pada Perusahaan Sektor Barang Baku dan Barang Konsumen Primer yang terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Wellson Glensius Mahulae; Herry Laksito (Diponegoro Journal of Accounting, 2026)
The manufacturing sector, specifically Basic Materials and Consumer Non Cyclicals, recorded a performance slowdown amidst a surplus in national tax revenue targets during the 2019-2023 period. This anomaly indicates a risk of tax avoidance behavior when companies face financial pressure. Furthermore, previous research findings regarding financial determinants of tax aggressiveness remain highly inconsistent. Therefore, this study aims to empirically analyze and examine the effect of profitability, leverage, and firm size on tax avoidance practices within these sectors. This research employs a quantitative approach utilizing secondary data from audited annual financial statements. The population includes all Basic Materials and Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Sample selection applied a purposive sampling technique based on positive earnings and data completeness criteria, yielding 230 observation units. Tax avoidance is proxied by the Cash Effective Tax Rate (CETR), profitability by Return on Assets (ROA), leverage by the Debt to Equity Ratio (DER), and firm size by the natural logarithm of total assets. Data analysis was conducted using multiple linear regression methods processed via SPSS after fulfilling classical assumption tests. Statistical testing results demonstrate that profitability, leverage, and firm size simultaneously do not affect the level of tax avoidance. Partial testing indicates that profitability has no significant effect, signifying that entities did not experience extreme profit spikes that typically trigger the need to practice aggressive tax planning. Leverage also proves to have no significant effect because the majority of companies utilize debt purely for operational expansion and working capital rather than engineering it as a tax shield scheme. Firm size similarly shows an insignificant result, indicating that large-scale entities tend to maintain tax compliance levels due to strict public scrutiny and high penalty risks from regulatory authorities.